Positive implicative True-False ideals in BCK-algebras - Rajabali Borzooei; M. Mohseni Takallo; Young Bae Jun; M. Aaly Kologani (Journal of Mahani Mathematical Research)
In BCK-algebra, the concept of a positive implicative $T&F$-ideal is introduced, and further several properties are investigated. The relationship between $T&F$-ideals and positive implicative $T&F$-ideals is established, and an example is given to reveal that a $T&F$-ideal is not a positive implicative $T&F$-ideal. Various conditions under which a $T&F$-ideal can be a positive implicative $T&F$-ideal are explored and various characterizations of a positive implicative $T&F$-ideal are studied. The extended property of a positive implicative $T&F$-ideal is constructed.